2018
DOI: 10.1017/s0950268818002984
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of incidence and geographical distribution of Chagas disease in Mexico during a decade (2007–2016)

Abstract: Chagas disease, whose aetiological agent is the protozoan Trypanosoma cruzi, mainly occurs in Latin America. In order to know the epidemiology and the geographical distribution of this disease in Mexico, the present work analyses the national surveillance data (10 years) for Chagas disease issued by the General Directorate of Epidemiology (GDE). An ecological analysis of Chagas disease (2007–2016) was performed in the annual reports issued by the GDE in Mexico. The cases and incidence were classified by year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…However, several studies have shown a higher frequency of infection in men aged 25-49 years, not only in general population serosurveys but also in reactivity studies in blood donors. This suggests that there seems to be a differential risk that some authors have explained from an occupational point of view [13,[25][26][27]. As for women of childbearing age, the collection of reactive sera is very timely in preventing congenital disease, taking into account that this represents up to 5% of all forms of transmission [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown a higher frequency of infection in men aged 25-49 years, not only in general population serosurveys but also in reactivity studies in blood donors. This suggests that there seems to be a differential risk that some authors have explained from an occupational point of view [13,[25][26][27]. As for women of childbearing age, the collection of reactive sera is very timely in preventing congenital disease, taking into account that this represents up to 5% of all forms of transmission [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…The design and data collection study were carried out according to Ibáñez-Cervantes et al [15]. Briefly, the monthly and annual reports of cases of pulmonary and MTB between 2007 and 2017 were published by the GDE and were analyzed in an observational and retrospective manner.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of variance (ANOVA) was also calculated in order to evaluate significant differences over time ( p =0.05), per data/year and month. A national distribution map showing the pulmonary and MTB incidence during the analyzed period was generated [15].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of infected vector and human infection with cases of Chagasic heart disease has been reported. [9][10][11] Additionally, previous studies demonstrated the presence of different DTUs (TcI-TcV) in domiciliated vectors in Orizaba and Cordoba, both cities in the central part of Veracruz. 12 However, the presence of T. cruzi DTUs in sylvatic vectors has not been studied.…”
Section: Introductionmentioning
confidence: 91%